Um estudo sobre a aceitação e utilização de Software Livre e de Código Aberto na Universidade Federal do Ceará com base na aplicação do modelo UTAUT - Lustosa, Marllus de Melo (2018)
The prioritization of the use of Free Software and Open Source (FOSS) contributes not only to the reduction of public spending, but also opens new doors in the fields of production and circulation of knowledge, through the gain of technological independence, in the training of public servants , in stimulating software development in collaborative environments and improving national technology. For this, the literature is ample to reporting that in order to achieve success in the implantation of a software or technology in an organization, it is necessary to analyze the behavioral variables of the users of these technologies, which represents a great point for success or failure in its implementation. In this way, the FOSS acceptance was investigated by the servers of the Federal University of Ceará (UFC), where 349 employees participated in a survey, which corresponded to the Administrative Technicians and Teachers referring to the three campuses of the city’s UFC of Fortaleza-CE (Pici, Benfica and Porangabuçu). The instrument of data collection was elaborated from the constructs of the UTAUT (Unified Theory of Acceptance and Use of Technology) model. Data analysis and treatment were performed through descriptive analysis, Confirmatory Factor Analysis (AFC), student’s t test, Analysis of Variance (ANOVA) and Data Mining (machine learning) . The AFC indicated that there was a reduction of the empirical data in 4 factors, recommended by the UTAUT model, and that these explained together 63% of the data variance. Two hypotheses proposed in the research were accepted, regarding the influence of the experience with the use of FOSS in the Expectations of Effort and Facilitating Conditions. The Data Mining technique generated 13.354 associations between the variables of the study. In one of the analyzes, it was evidenced that the effect of the construct Performance Expectation is stronger in young adult male workers (78 to 80%), while it is lower in females (63 %), in addition to more experienced servers in the use of these tools (71%) are more convinced that they have the resources and knowledge needed to use them, corroborating with the one described in the theoretical model.